(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
It is no exaggeration to say that terminology is the brain of all fields. It is impossible to imagine the field of medicine without terms. This article talks about the linguistic features, uniqueness, translation mechanism of the terms used in English and Uzbek languages.